Combinatorial Analysis of AT-Rich Interaction Domain 1A and CD47 in Gastric Cancer Patients Reveals Markers of Prognosis - Zhao, Qianfu; Cai, Qu; Yu, Shanhe; Ji, Jun; Zhu, Zhenggang; Yan, Chao; Zhang, Jun (Frontiers in Cell and Developmental Biology, 2021)
Background: The AT-rich interaction domain 1A (ARID1A) is thought to be a tumor suppressive gene, and most mutation of ARID1A results in loss expression of ARID1A protein. CD47 combined with signal-regulatory protein alpha (SIRPα) constitutes the “Don’t eat me” signal to help tumors avoid immune surveillance. However, the relationship between ARID1A and CD47 expression, and their prognostic value in gastric cancer were unknown. Methods: In this study, we evaluated ARID1A and CD47 expression in 154 gastric cancer patients tissues with tissue microarray. Expression of ARID1A and CD47 in cell lines were determined by Western blot and qRT-PCR, cell membranous CD47 expression were quantified by flow cytometry. Tumor-infiltrating immune cells was estimated on TCGA data set by quanTIseq and EPIC algorithms. Results: A significant correlation was found between loss of ARID1A and high CD47 at translation level in gastric cancer. Integrating 375 bulk RNA sequencing samples from TCGA data set, we found mutated ARID1A correlates with high CD47 expression. In GC cell lines, knockdown of ARID1A significantly increased CD47 expression both at protein and mRNA level measured by Western blot, flow cytometry and qRT-PCR. Utilizing univariate and multivariate survival analysis, we found patients with CD47highARID1Aloss expression had worse prognosis. Estimation of infiltrating immune cells on TCGA data set showed that higher infiltration proportion of regulatory T cells (Tregs) was found in CD47highARID1Amutated expression subgroup. Conclusions: In conclusion, loss of ARID1A was tightly correlated with high CD47 expression in gastric cancer, and combination of ARID1A and CD47 is a promising prognosis factor in gastric cancer.